An Overview of Theories and Issues on Vocabulary Learning Strategies in The Second Language Learning - Temmy, Temmy (Humaniora, 2012)
The research on language learning theories played important role in TCFL research. Article sorts out and summarizes the issues and theories on second language learning and vocabulary learning?s strategies from both Western and Chinese scholars. It can be summarized that  Western scholars have started a broad scope research in vocabulary learning strategies since their early times, then, the research? results have helped to give a solid and important foundation for the development of vocabulary learning strategies nowadays. Even though TCFL scholars have realized the importance of vocabulary learning strategies in the process of second language learning and more research are being done, but until now, the amount and quality of research in this field still needs to be improved. There is still a big space in the diversity perspective of research that needs to be filled. Article presents  the history and development of the theories of vocabulary learning strategies to help impel and deepen the research of TCFL.